Molecular epidemiology and antibiotic resistance of group B Streptococcus in pregnant women and neonates from Haikou, China: implications for vaccine development and antimicrobial stewardship - Mai, Wenhui; Wang, Huiting; Meng, Qiaoyi; Zhang, Jingyi; Gong, Xinyi; Zhuo, Zhulin; Sui, Jinlei; He, Xiaowen; Wang, Yan; Li, Juan; Xu, Jianping; Wu, Jinyan (Frontiers in Cellular and Infection Microbiology, 2025)
Group B Streptococcus (GBS) is a major cause of pregnancy complication and neonatal morbidity and mortality worldwide, particularly in developing regions. Despite its clinical importance, data on the molecular epidemiology, antibiotic resistance, and virulence factors of GBS in tropical regions are scarce. This study provides the first comprehensive analysis of GBS strains from pregnant women and neonates in Haikou, a tropical city in China, via antibiotic susceptibility testing and whole-genome sequencing. Our results grouped the 138 strains of GBS into seven serotypes and 28 multilocus sequence types (STs). These STs belonged to six clonal complexes (CCs). High antibiotic resistance rates were observed for tetracycline (89.1%) and clindamycin (55.1%) and the commonly detected resistance genes included mreA (100%), ermB (52.9%) and tetM (41.3%). Each strain contained at least one Pili-island (PI) gene and the capsular polysaccharide antigen among the GBS isolates were variably associated with CCs. All strains carried virulence genes cfb and cylE, followed by pavA (99.3%), and lmb (66.7%) etc. Our analyses showed ST862 as a dominant and potentially zoonotic genotype in Haikou, China, with implications for both human and animal health. The high prevalence of tetracycline and clindamycin resistance underscores the need for judicious antibiotic use and the development of region-specific antibiotic treatment guidelines. The discovery of novel STs and broad distributions of several virulence factors provide valuable insights for future vaccine development and targeted interventions in this region.